2010
DOI: 10.1128/aac.00572-10
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectrum of the Neoglycoside ACHN-490

Abstract: ACHN-490 is a neoglycoside, or "next-generation" aminoglycoside (AG), that has been identified as a potentially useful agent to combat drug-resistant bacteria emerging in hospitals and health care facilities around the world. A focused medicinal chemistry campaign produced a collection of over 400 sisomicin analogs from which ACHN-490 was selected. We tested ACHN-490 against two panels of Gram-negative and Grampositive pathogens, many of which harbored AG resistance mechanisms. Unlike legacy AGs, ACHN-490 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
215
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(227 citation statements)
references
References 20 publications
(14 reference statements)
4
215
0
2
Order By: Relevance
“…AAC(3)-IV is known to confer gentamicin and tobramycin resistance among clinical strains of Escherichia coli (35), but to our knowledge, it has not been reported previously in K. pneumoniae or significantly associated with higher plazomicin MICs. Our findings suggest that the 1-Nhydroxyaminobutyric acid within plazomicin may not confer full protection from inactivation by AAC(3)-IV (12). APH(3=)-Ia cannot modify plazomicin because the drug lacks the target 3=-OH group, and it has not been linked to resistance to any of the agents in this study.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…AAC(3)-IV is known to confer gentamicin and tobramycin resistance among clinical strains of Escherichia coli (35), but to our knowledge, it has not been reported previously in K. pneumoniae or significantly associated with higher plazomicin MICs. Our findings suggest that the 1-Nhydroxyaminobutyric acid within plazomicin may not confer full protection from inactivation by AAC(3)-IV (12). APH(3=)-Ia cannot modify plazomicin because the drug lacks the target 3=-OH group, and it has not been linked to resistance to any of the agents in this study.…”
Section: Discussionmentioning
confidence: 63%
“…Plazomicin, a derivative of sisomicin, is a next-generation aminoglycoside that is in clinical development for the treatment of serious infections due to carbapenem-resistant Enterobacteriaceae. It has broad-spectrum in vitro activity against Klebsiella pneumoniae and other Gram-negative bacteria, including carbapenem-resistant strains (8)(9)(10)(11)(12). The agent has side-chain substituents that shield it from the action of most AMEs.…”
mentioning
confidence: 99%
“…6′-N-Cbz-TOB (20) was prepared from the reaction of TOB and compound 3, using potassium carbonate as a base in a 1:1 mixture of H 2 O and MeOH. It is important to note that an attempt at using O-Cbz-N-hydroxysuccinimide instead of compound 3, did not yield any of the desired compound 20.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…They were also moderately active (MIC = 8 μg/mL) against S. aureus ATCC 29213 (E). Testing of the 6′-N-Cbz-TOB (20) suggested that having an amine in the group added to the parent AG scaffold is greatly beneficial as 20 was found to be inactive against almost all bacterial strains tested.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
See 1 more Smart Citation